Research on disaster mechanism and correlation of natural earthquake and coal and gas outburst - Rong, Hai; Yu, Shiqi; Song, Weihua; Tang, Guoshui; Wang, Yadi; Sun, Dequan; Huo, Bingjie (Frontiers in Earth Science, 2023)
In recent years, with the increasing of mining depth and mining intensity, coal and gas outburst has become one of the most destructive and harmful dynamic disasters in coal mines. Natural earthquakes are the most destructive natural disasters in the earth’s crust. Both of coal and gas outbursts and natural earthquakes are caused by geo-dynamic processes. In order to research the correlation between coal and gas outburst and natural earthquake, in this manuscript, we took Pingdingshan eastern mining area as the research object. The principles of disaster prevention, seismology, statistics and geophysics were taken as the research basis, both the characteristics and laws of natural earthquakes, and the occurrence laws and characteristics of coal and gas outburst were systematically analyzed by geo-dynamic division method. At the same time, the relationship between the two disasters were established. The research results show that natural earthquake is the accumulation and release process of elastic properties in rock mass, which can induce the abnormal emission of gas in coal mines under specific conditions. Especially the “weak plane structure” in geological structure, which is more likely to lead to the occurrence of coal and gas outburst accidents. Tectonic activities and stress field changes have a unified mechanism for the occurrence of natural earthquake and coal and gas outburst, there are correlations between space and intensity. The research results can also provide new ideas for the prediction work of these two kinds of disasters.